The use of chairside silica coating for different dental applications: A clinical report - (:unkn) unknown (MOSBY-ELSEVIER, 2002)
This article describes an alternative approach to conditioning an alloy surface prior to veneering with composite, The procedure is based on silica coating and silanization of the alloy surface, which can be performed chairside.
Keywords: RESIN-BONDED RETAINERS; COMPOSITE BOND; PORCELAIN; STRENGTH; METAL; POSTS; REPAIR; SYSTEM; SHEAR; CORES